2010
DOI: 10.1073/pnas.0906829107
|View full text |Cite
|
Sign up to set email alerts
|

Sustaining multiple ecosystem functions in grassland communities requires higher biodiversity

Abstract: Society places value on the multiple functions of ecosystems from soil fertility to erosion control to wildlife-carrying capacity, and these functions are potentially threatened by ongoing biodiversity losses. Recent empirically based models using individual species’ traits suggest that higher species richness is required to provide multiple ecosystem functions. However, no study to date has analyzed the observed functionality of communities of interacting species over multiple temporal scales to assess the re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

21
406
2
10

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 414 publications
(439 citation statements)
references
References 21 publications
21
406
2
10
Order By: Relevance
“…Email: fonsvanderplas@gmail.com. diversity-multifunctionality relationship is often used as an argument to promote biodiversity conservation (6,10). However, although society seeks to maximize the delivery of potentially conflicting ecosystem services, such as food production, bioenergy generation, and carbon storage at the landscape scale (11)(12)(13), research into the relationship between biodiversity and ecosystem multifunctionality has been largely limited to local-scale studies, where diversity is manipulated in experimental plant communities.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Email: fonsvanderplas@gmail.com. diversity-multifunctionality relationship is often used as an argument to promote biodiversity conservation (6,10). However, although society seeks to maximize the delivery of potentially conflicting ecosystem services, such as food production, bioenergy generation, and carbon storage at the landscape scale (11)(12)(13), research into the relationship between biodiversity and ecosystem multifunctionality has been largely limited to local-scale studies, where diversity is manipulated in experimental plant communities.…”
mentioning
confidence: 99%
“…β-diversity | biodiversity | ecosystem functioning | FunDivEUROPE | spatial scale I t is widely established that high local-scale biodiversity increases levels of individual ecosystem functions in experimental ecosystems (1)(2)(3)(4), and that biodiversity is even more important for the simultaneous maintenance of multiple functions at high levels (i.e., ecosystem multifunctionality) (5)(6)(7)(8). Because the capacity of natural ecosystems to maintain multiple functions and services is crucial for human well-being (9), the positive Significance Numerous studies have demonstrated the importance of biodiversity in maintaining multiple ecosystem functions and services (multifunctionality) at local spatial scales, but it is unknown whether similar relationships are found at larger spatial scales in real-world landscapes.…”
mentioning
confidence: 99%
“…Bonferroni corrections were used to account for multiple comparisons in the post hoc analyses (Abdi, 2007). We also assessed associations between the collective extents of pharmaceutical biotransformation and biodiversity by scaling each compound's normalized extent of loss (mean of 0, standard deviation of 1) (Zavaleta et al ., 2010). Two‐sided Spearman rank correlation was used to test associations between biodiversity measurements and pharmaceutical biotransformation extents.…”
Section: Methodsmentioning
confidence: 99%
“…Such a biodiversity is crucial for maintaining ecosystem multifunctionality (i.e. the ability of ecosystems to maintain multiple functions and services simultaneously, such as carbon storage, productivity and the build-up of nutrient pools [18]), as suggested by recent studies carried out with vascular plants and BSCs worldwide [19 -22]. Moreover, drylands also display a wide array of vegetation (figure 1) and soil types.…”
Section: Dryland Ecosystems: Definition and Importancementioning
confidence: 99%